PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI GURU TERHADAP MUTU LAYANAN DI SMK - Wiretno, Indro; Chiar, M; Syukri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTo make a quality school requires a process by providing a best service and quality to customers. provision of service at school depend on the ability of a leader who called Principal. The principal has a very important role in influencing his subordinates to be able to work together on achieving the goal that has been settled. Provision of quality service at school is very coveted by all citizens of the school and community. Provision of service at school is one of form of the needs of citizens at school and surrounding communities in increasing the needs of school facilities and infrastructure. The factors that can affect the quality of school services in an effort to make a quality school in this research, that is principal leadership and teacher motivation. The aim of this research to determine the influence of principal’s leadership and teacher’s motivation toward the quality of State Vocational High School service in Subrayon 1 Sambas Regency.This research suggest 1) to give maximum result in quality school management by giving service to customer, 2) to crate qualified graduates, in teaching and learning process at school, the teacher should give the best service and learning motivation to the students. 3) principals, teachers and staffs that exist in the school environment provide treatment in serving students, parents and community that priority to customer service satisfaction in the form of prime service. 4) in this research has explained that the quality of service provided by the principal to customers and teachers motivation to the students in learning will be affect to the quality of the school. Keywords : Principal’s Leadership, Teacher’s Motivation, quality